Kelayakan Finansial Pemasaran Digital Stroberi Organik Saat Pandemi Covid-19 di SFI, Magelang, Jawa Tengah - gandhi, prima - (MuJAgri: Musamus Journal of Agribusiness, 2022)
No party can confirm when the spread and pandemic of Corona Virus Disease-2019 (Covid-19) will end. In addition to having an impact on health, Covid-19 has an impact on economic growth. One sector that continues to grow positively during the pandemic is the agricultural sector. The optimization of digital marketing by agricultural commodity producers is the key to this positive growth. SOGA Farm Indonesia (SFI) is one of the producers of organic strawberries in Indonesia. SFI carries out activities from providing input to marketing to consumers. Marketing carried out by SFI is personal selling and conventional. During the pandemic, SFI plans to optimize digital marketing. The application of digital marketing that will be carried out is to combine the website and Instagram social media. The purpose of this study is to analyze the financial aspects of business development in the form of digital marketing at SFI. The analytical method used is descriptive graphical tabulation and quantitative includes revenue analysis, profit/loss analysis, R/C ratio analysis. Based on the financial analysis carried out, the results obtained in the form of an increase in revenue of Rp. 158,899,200, an increase in profit of Rp. 50,364,317, and the value of the R/C ratio of 1.5. From the financial analysis, it is concluded that digital marketing efforts are feasible because it will provide benefits during the Covid 19 pandemic for SFI. Digital marketing optimization is a practice to support the 8th Sustainable Development Goals (SDGs).